1984
DOI: 10.1080/09593338409384296
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of simple phenols in oil sands extraction‐process water

Abstract: A simple aqueous acetylation method was successfully applied to the analysis of ppb to low ppm levels of phenolic compounds in waste-waters from the Syncrude Canada Ltd. oil sands plant in northern Alberta. Phenolics in process-affected waters, as well as surface and ground waters were extracted as acetate derivatives from aqueous solution, quantitated by FID-GC and identified by GC-MS. Phenol, cresols and several other alkylphenols were identified in tailings pond waters whereas only traces of phenol and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…O1 compounds may be alkylphenols and have been shown to be present in OSPW at ppb to low ppm concentrations. 28 The formula of the C 15 O1 compound (C 15 H 24 O) is consistent with that of nonylphenol. Alkylphenols are thought to contribute significantly to endocrine disruption.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…O1 compounds may be alkylphenols and have been shown to be present in OSPW at ppb to low ppm concentrations. 28 The formula of the C 15 O1 compound (C 15 H 24 O) is consistent with that of nonylphenol. Alkylphenols are thought to contribute significantly to endocrine disruption.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…O1 compounds may be alkylphenols and have been shown to be present in OSPW at ppb to low ppm concentrations. 28 The formula of the C 15 O1 compound (C 15 H 24 O) is consistent with that of nonylphenol. Alkylphenols are thought to contribute significantly to Thomas et al 11 showed that 35% of the estrogenic activity could be attributed to petrogenic alkylphenols in off-shore North Sea discharge waters.…”
Section: Environmental Science and Technologymentioning
confidence: 58%
See 2 more Smart Citations
“…NA surrogates and estradiol utilisation in microtiter respirometry assay Carbon substrates in OSPW are oil and grease (25 ± 15 mg/L) (MacKinnon and Boerger 1986), NAs (20-120 mg/L) (Frank and Kavanagh 2008) and minor amounts of alkylphenols (\0.3 mg/L) (Hargesheimer et al 1984) and PAHs (10 lg/L) (Rogers et al 2002). Although NAs, alkylphenols and PAHs are known to be toxic, the latter two are at relatively low concentrations; hence this study focused on NAs.…”
Section: Toxicity Of Nas Surrogates and Estradiolmentioning
confidence: 99%